Management of High-Grade Penile Curvature Associated With Hypospadias in Children - Moscardi, Paulo R. M.; Gosalbez, Rafael; Castellan, Miguel Alfedo (Frontiers in Pediatrics, 2017)
Penile curvature is a frequently feature associated with hypospadias with also a great variability of severity among each patient. While the low-grade curvature (<30º) can be relatively easily corrected by simple techniques like penile degloving and dorsal plication, severe cases often demand more complex maneuvers to manage it. A great number of surgical techniques have been developed to adequately correct curvatures greater than 30 degrees, however each one of them should be individualized to different patients and local conditions encountered. In this article, we will review the evaluation of the pediatric patient with penile curvature associated with hypospadias with a special attention to high-grade cases, their management, indications for surgical treatment and several surgical options for their definitive treatment.